140k views
3 votes
Y = -3x + 10
Y = -2x + 6

The solution to this system is ( ? , ? )

User Sunus
by
4.1k points

1 Answer

3 votes

Answer:

(4, -2)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination

Explanation:

Step 1: Define Systems

y = -3x + 10

y = -2x + 6

Step 2: Solve for x

Substitution

  1. Substitute in y: -3x + 10 = -2x + 6
  2. Add 3x on both sides: 10 = x + 6
  3. Isolate x: 4 = x
  4. Rewrite: x = 4

Step 3: Solve for y

  1. Define equation: y = -2x + 6
  2. Substitute in x: y = -2(4) + 6
  3. Multiply: y = -8 + 6
  4. Add: y = -2
User CPI
by
5.0k points